KONTRIBUSI BEBAN KERJA, DISIPLIN KERJA, HUBUNGAN DENGAN TEMAN SEKERJA TERHADAP PRODUKTIVITAS KERJA DI PT. VICCON MODERN INDUSTRY - NUR AFIA, IKA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Company is a profit oriented organization that concerned about productivity so much. In certain condition still found unhealthy working condition, including the workload determination, work discipline and coworker relationship building that resulted in the unequal job distribution, rules violations and poor working relationships that will affect the productivity.This research is a quantitative explanation research that aims to determine the contribution of workload, work discipline, and coworker relationship to the work productivity in PT. Viccon Modern Industry eather partially or simultaneously. This research uses saturation sampling because  the amount of respondents are 65 workers. Test was performed by  t-test and F-test using SPSS for Windows version 16.0. Simultaneously, the test results show that workload, work discipline, and coworkers relationships contributed positively to the work productivity. Partially, the test results show that workload contributed positively to the work productivity. Work discipline contributed positively to the work productivity. Coworkers relationships  contributed positively to the work productivity.    Keywords : workload, work discipline, coworker relationship, work productivity